Camila the record-breaking star - Salazar, Alicia, 1973- (Salazar, Alicia, 1973- Camila the star., 2021)
Camila dreams of being a star and, after learning about children who break world records, decides she will do the same--but how? Includes glossary, glossary of Spanish words, activities, and discussion questions.